I'm stuck:
a. 4(x squared) + 12x + 3 = 0
b. 2x + 1 = 5 divided by (x + 2)
c. [(x + 1) divided by x ] - [x divided by (x + 1)] = 0
Here ya go
$\displaystyle 4x^2+12x+3=0$
using the quadratic formula let a=4, b=12 and c=3 we have
$\displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$
so
$\displaystyle x=\frac{-12\pm\sqrt{(12)^2-4(4)(c)}}{2(4)}$
you can do the rest.
As for the next one
$\displaystyle 2x+1=\frac{5}{x+2}$
multiply both sides by (x+2) and then subtract by 5
$\displaystyle (x+2)(2x+1)-5=0$
multiply and simplify
$\displaystyle 2x^2+5x-3=0$ and use the quadratic formula. I'll leave the last one to you
Hint : find a common denominator and then multiply both sides of the equation by it.
for equations in the form $\displaystyle ax^2+bx+c = 0$ to find zeros you can apply
$\displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$
For $\displaystyle 4x^2+12x+3 = 0$ you make $\displaystyle a=4, b=12,c=3$ therefore
$\displaystyle x=\frac{-12\pm\sqrt{12^2-4\times 4\times 3}}{2\times 4}$
go fot it!